Data journalism in Turkey: Developing a scale and measuring journalists' skills - BAYRAKCI, SERKAN; ÖZAY, SEÇİL (My University, 2022)
Data journalism has recently emerged as an important method of news gathering and editing in journalism. For data journalism which includes the process of producing news from data journalists need to have various skills and competencies. As a result of the literature review, it is observed that the required skills and competencies for data journalism have not been determined precisely, and in this regard, there is a lack of quantitative studies to measure these skills and competencies of data journalism. This study aims to develop a unique scale that will reveal the data journalism skills of news producers. For this purpose, a data journalism scale has been developed through an online survey applied to news producers registered with the Turkish Press Agency (BIK). As a result of the item pool, expert views, and the scale application stages, it is understood that data journalism skills can be measured with a 2-factor structure: \"data skills and tools\" and \"journalism skills.\" The Cronbach Alpha reliability coefficient for the overall 21-item data journalism scale was calculated as 0.856, the data skills and tools factor as 0.883, and the journalism skill factor as 0.821. As a result of the research, it has been determined that while the journalism skills of the news producers are at a high level, their competence in data processing is low. In this sense -as a result of the study- a revision is recommended in both academic and professional training curriculum to include data collection, analysis and visualization skills that will improve data skills of news producers.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; SOSYAL BİLİMLER, İNTERDİSİPLİNER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SOCIAL SCIENCES, INTERDISCIPLINARY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Sosyal Bilimler (çeşitli); Genel Sosyal Bilimler; Teknoloji ve İnovasyon Yönetimi; Yönetim Bilgi Sistemi; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences (miscellaneous); General Social Sciences; Management of Technology and Innovation; Management Information Systems; Social Sciences & Humanities; Data journalism; data; data skills; journalism; scale development; data journalism scale